Acupuncture Legislation in the United States: Minnesota as a Case Study - Changzhen Gong; Zhiheng GUO (Wolters Kluwer Health/LWW, 2024)
Abstract. 2023 marks the 50th anniversary of legal regulation of acupuncture in the United States, as the first acupuncture law was enacted in Nevada. Acupuncture, like any other medical modality, is regulated at the state level, with each state formulating and enforcing its own laws and statutes over time. This article narrates the legislative process and major developments of the acupuncture profession in Minnesota, in the context of legislative developments across the country. It tells how this midsize, Midwest state's acupuncture profession became regulated, and examines the challenges faced by the profession before and after state statutes were enacted. Minnesota stands as a representative example of the legislative process in other states.